Analisis Feminisme Dan Dekontruksi Citra Perempuan Pada Tokoh Hanum Dalam Novel Faith & The City - Nur Dina Camelia; Rozaiqah Noer Marisah; Siti Afiyana; Mas’odi Mas’odi (Pusat Riset dan Inovasi Nasional, 2025)
Literature provides a wide scope of meaning for its readers, including in assessing the role of women as wives, which can be seen as good or bad depending on the author's point of view. In one of the hadiths narrated by Bukhari, women are described as having responsibility for the affairs of their husbands and children in the household. However, in the novel